Waktu dan Cara Aplikasi Cendawan Mikoriza Arbuskular (CMA) pada Pertumbuhan Bibit Tanaman Kopi - Parapasan, Yonathan; Gusta, Adryade Reshi (Jurnal Penelitian Pertanian Terapan, 2014)
The effort to increase productivity of coffee plants in long dry season upland of Ultisol include application of Vesicular Arbuscular Mycorrhizae (VAM) on coffee plants, because its application only one time and its affect along a life time of coffee plant in the field. This study aims to determine the exact time and applications method of VAM on growth coffee seedlings. This study used 10 g VAM/polybag or 800 spores as basic treatment. This study used randomized block design and experiment arranged in factorial 3 x 5 with three replications. The first factor was the time of VAM application: given at nursery seedlings (W1), given at transplanting (W2), and combine of given at nursery seedlings and transplanting (W3). The second factor was the applications method of VAM: without VAM inoculant (C0), VAM inoculant placed around the coffee seedling root up to a depth of 2 cm below root (C1), up to a depth of 4cm below root (C2), up to a depth of 6 cm below root (C3), and VAM inoculant mixed with media planting (C4). All data were analyzed for variance. Data analysis followed by separation of means using LSD test with significance level of 5%. The resulted showed that both time and applications method of VAM have affect on growth component and root infection rate. The best application time was double application, i.e. combine of given at nursery seedlings and transplanting, and the best applications method was VAM inoculant placed around the coffee seedling root up to a depth of 2 cm below root, both of them increased plant height, stem diameter, leaf amount, long of root, and root infection rate.